Strongly improved mechanical properties of aluminum composites by designed ceramic lattice - Zijian Zhang; Wanyu Li; Yingjie Feng; Xiangyang Liu; Xuefei Zhang; Yujia Huang; Keqiang Zhang; Chunlei Wan (Journal of Materials Research and Technology)
Achieving a balance between high strength and ductility in structural materials is a formidable challenge. This study introduces an innovative, designable interpenetrating ceramic-metal composite, produced through additive manufacturing (AM) and gas pressure infiltration. Such an approach significantly enhances the matrix's strength by a factor of 3, while preserving its ductility. The design flexibility afforded by AM in crafting the reinforcement structure is crucial for the performance of the composites. It mitigates stress concentrations and amplifies the synergistic interaction between the ceramic and metal phases, leading to an optimization of the mechanical properties. The composite exhibits superior dimensional stability under high-stress cyclic loading conditions, surpassing the matrix's susceptibility to excessive plastic deformation. Furthermore, the wear resistance of the composite is markedly improved, with reduced wear loss under elevated load conditions. These findings demonstrate the potential of designable composite for applications in aerospace, automotive, mechanical systems, and other fields that require high strength, enhanced wear resistance, and lightweight properties.